Mound‐forming cold‐water corals and bryozoans in the Early Palaeocene of Denmark. Issue 4 (11th December 2017) - Bjerager, Morten; Sheldon, Emma; Lauridsen, Bodil W.
Abstract: The Faxe Quarry in south‐east Denmark offers excellent exposures of Early Palaeocene, Danian deep‐water intercalated coral and bryozoan mounds that form complexes at least 40 m thick and a few kilometres wide along and over submarine highs. The coexisting coral and bryozoan mounds represent two different biogenic carbonate factories with a highly dynamic interplay during growth. The sedimentary facies, mound geometries and the density, diversity and palaeoecology of the associated benthic invertebrates and nannofossils allow recognition of six successive growth units. Unit 1 represents an outer shelf bryozoan mound belt characterized by an oligotrophic cool‐water nannofossil assemblage. Unit 2 comprises a mixed faunal assemblage of bryozoans and octocorals with an initial sparse colonization of hexacorals. The nannofossil assemblage records a decrease in diversity and an increase in warm water forms. Unit 3 marks the onset of dense colonization of the scleractinian coral Dendrophyllia candelabrum with associated low‐diversity macrofauna and nannofossil assemblages. Unit 4 represents the main coral build‐up phase with frame‐building hexacorals of Dendrophyllia and Faxephyllia associated with a high‐diversity invertebrate fauna, and relatively low‐diversity nannofossil assemblages. Unit 5 represents the late coral mound phase showing extensive lateral distribution and finally death and erosion of the coral mounds. This event was contemporaneous with a warming trend in the pelagic environment. The succeeding Unit 6 marks the burial and overgrowth of the coral mound complex by bryozoan‐rich sediments. The coral mound complex in the Faxe Quarry initiated and terminated in global nannofossil zone NP3 and regional nannofossil zones NNTp2G–3 suggesting a mound growth duration of ca 300 kyr and a mean vertical accretion of the coral mound of 13 cm kyr −1 . The mound complex probably serves as the best‐exposed analogue to modern deep and cold‐water coral mounds in the North Atlantic.